The effect of creating workplace fun on employees’ job satisfaction, commitment and turnover - Al Bazzal, Hala (2021)
This paper aims at exploring the effect of workplace fun on employees’ job satisfaction, commitment and turnover. First, the concept of workplace fun, employees’ job satisfaction, commitment and turnover will be introduced. Second, the derivers, types, features and consequences of workplace fun will be discussed. Gender diversity toward workplace fun was also considered in this paper as well as the factors and effects of employee’s job satisfaction. Then, the types, factors and consequences of commitment at the individual and organizational levels were shown. After this, turnover types, factors and ways to reduce it were listed too. This paper also contributes by studying the theoretical framework and the relationships between the variables. Then a survey was developed and empirically tested using data collection through an online questionnaire. The survey was sent to currently employed individuals in the Lebanese sector. A total of 250 employees had completed the survey and their data was analyzed with an SPSS program. The results demonstrated that having fun at the workplace has an impact on the three variables discussed in the study. This paper adds value to the literature gap since there is a limited research that exists on this topic especially because it’s known to be a new topic in the HR field.